Analysis of vesicular monoamine transporter 2 polymorphisms in Parkinson’s disease - Brighina, Laura (Elsevier, 2013)
Generation of reactive oxygen species during dopamine (DA) oxidation could be one of the factors leading to the selective loss of nigral dopaminergic neurons in Parkinson’s disease (PD). Vesicular monoamine transporter type 2 (VMAT2) proteins in nerve terminals uptake dopamine into synaptic vesicles, preventing its cytoplasmic accumulation and toxic damage to nigral neurons. Polymorphisms in VMAT2 gene and in its regulatory regions might therefore serve as genetic risk factors for PD. In the present study, we have analyzed 8 single-nucleotide polymorphisms (SNPs) located within/around the VMAT2 gene for association with PD in an Italian cohort composed of 704 PD patients and 678 healthy controls. Among the 8 SNPs studied, only the 2 located within the promoter region (rs363371 and rs363324) were significantly associated with PD. In the dominant model, odds ratios were 0.72 (95% confidence interval [CI]: 0.6–0.9, p < 0.005) for rs363371 and 0.76 (95% CI: 0.6–0.9, p = 0.01) for rs363324; in the additive model, odds ratios were 0.78 (95% CI: 0.65–0.94, p = 0.008) for rs363371 and 0.85 (95% CI: 0.7–20.92, p = 0.04) for rs363324. There were no significant relationships between the remaining SNPs (rs363333, rs363399, rs363387, rs363343, rs4752045, and rs363236) and the risk of sporadic PD in any genetic model. This study adds to the previous evidence suggesting that variability in VMAT2 promoter region may confer a reduced risk of developing PD, presumably via mechanisms of gene overexpression.